ZapinApi di Teluk Rhu, Tinjauan Bentuk dan Fungsi - Susi Vivin Astuti (EKSPRESI, 2009)
Zapin Api at The Rhu Bay: a Study of Form and Function. This paper discusses the form and function of lapin Api show at the Rhu Bay. They were collected by observation and interview with the lapin players and the prominent figures of the local society. The research result showed that the show shifted in terms of form and function. In earlier times, the show was meant to honor the ancestors' spirit, called Noyang Kacang in order to ask the spirits to guard the people in the hard times in their life cycle such as birth, marriage, and death. Now, this show functions in fulfilling the ritual and symbolic needs, in forming social integrity, and as entertainment. Keywords: Noyang Kacang, lapin, Rhu.